Systemic Lupus erythematosus - Epidemiology, Etiopathogenesis, Clinical Presentation, Cutaneous Manifestations and Treatment - A Systematic Review - Starczewski, Łukasz; Babik, Adrianna; Kamińska, Kamila; Będkowska-Kuśmierek, Matylda; Złotnik, Anna; Krzysztofik, Kinga; Klamka, Antoni; Kawalec, Paulina; Bronikowski, Kamil; Ryszkowski, Maksymilian (Quality in Sport, 2026)
Introduction. Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a complex etiopathogenesis and a highly diverse clinical presentation. The disease may involve multiple organs and systems, including the skin, kidneys, nervous system, and cardiovascular system. One of the characteristic features of the disease course are cutaneous manifestations, which may sometimes be the first symptom and can have important diagnostic value. Aim of the study. The aim of this study was to review the current literature on the epidemiology, etiopathogenesis, clinical presentation, and cutaneous manifestations of systemic lupus erythematosus, as well as to discuss contemporary treatment methods for this disease. Conclusions. Systemic lupus erythematosus is a disease of multifactorial etiology in which genetic, immunological, and environmental factors play an important role. The clinical presentation is highly heterogeneous, and skin lesions are among the most common and characteristic manifestations of the disease. Early diagnosis and appropriately selected treatment, including antimalarial drugs, glucocorticosteroids, immunosuppressive agents, and biological therapies, may significantly reduce disease activity and improve patients’ quality of life. Comprehensive management, including prevention of complications and appropriate multidisciplinary care, is also of great importance.